Leveraging the community development approach to examine the natural capital effect on sustainable development goal 3 - target 2. Issue 5 (20th October 2022) - Gani, Azmat
ABSTRACT: This study investigates if natural capital abundance matters for the United Nations Sustainable Development Goal (SDG) 3, Target 2, to reduce under-five mortality rates in 56 low and lower-middle-income countries. The empirical investigation is based on a health production conceptual framework using data for 2000, 2005, 2010 and 2014. The findings confirm that natural capital abundance has not translated into reductions in under-five mortality rates in any of the four-time periods. It is concluded that weaker economies with natural resource abundance should institute policies that target the sustainable extraction of natural capital and develop effective synergies with the extractive sector to improve child health and the timely achievement of SDG 3, Target 2.